La Interdisciplinariedad En El Aula De EducaciÃ³n Secundaria: Una InvestigaciÃ³n A TravÃ©s De La OpiniÃ³n Del Profesorado De Las Ãreas De MÃºsica, Lengua Castellana Y Literatura, Y Ciencias Sociales. - Arnal, Carmen M. Zavala; Salinas, Jorge RamÃ³n (European Scientific Journal, ESJ, 2017)
This paper shows the results of a study which analyzes daily practice through the opinion of teachers in Spain, which prompt us to consider the need for interdisciplinary activities. The study focuses on three areas: Music, Spanish Language and Literature, and Social Sciences. The results point at a favourable opinion of teachers regarding interdisciplinarity between the three subjects, although they highlight the obstacles arising from the curricular and educational context. The aim is to contribute to the integration in learning/teaching processes of interdisciplinary activities which can favour teachers as well as learners of these subjects.